Inquiry-Based Learning Strategies to Increase Primary School Students' Interest in Learning Pancasila and Citizenship - Dyra Amanda (International Journal of Students Education, 2024)
This research aims to evaluate the effectiveness of inquiry-based learning strategies in increasing elementary school students' interest in learning Pancasila and Citizenship Education (PPKn). The research method used in the literature study regarding inquiry-based learning strategies to increase elementary school students' interest in learning Pancasila and Citizenship involves several systematic steps. First of all, researchers search for relevant sources of information through academic databases, scientific journals, conferences and other related sources. The research results show that implementing inquiry-based learning strategies provides a significant positive impact. There has been an increase in student involvement in learning, where they are active in discussions, material exploration and problem solving. Apart from that, students' understanding of Pancasila and citizenship values has also increased, as can be seen from their ability to explain concepts better and relate them to everyday life. Apart from increasing engagement and understanding, this research also found an increase in students' intrinsic interest and motivation towards Civics learning. Students feel more enthusiastic and eager to learn, seek additional information, and actively participate in learning activities. Thus, it can be concluded that inquiry- based learning strategies are effective in increasing students' interest, involvement and understanding of Civics learning in elementary schools. Recommendations for further research are to continue applying inquiry methods, providing training to teachers, and integrating the context of students' lives in Civics learning, with the hope of forming the next generation who have good and responsible civic character.